Somalia: A Case Study in Nation Building - Elmi, Ahmed Hashi (2000)
Among Muslim nations, few have achieved an international standard of good governance. Somalia, completely dismembered by European colonial power, and now reduced to nearly total anarchy by the generation of post-independence rule, is desperately in need of help. After a thorough analysis of recent aid efforts, it is concluded that only the Somalis can rescue themselves. An in depth interview was conducted on a select group of Somali and Malaysian intellectuals and diplomats. A first-hand observation was organized into a chronology of events during the post-independence years, and then this data was analysed in detail. The thesis findings involve a two-fold failure. Almost unaccountably, President Siyad Bare's post-independence rule quickly degenerated from an Islamic ideology expressed in "scientific socialist" political form, into a totally anarchy involving the worst forms of corruption, nepotism and tribalism. This is The first failure in domestic nation building process. The second failure is the failure of the international community to render aid to the suffering and starving Somali people in any effective way. The panels of informants have elucidated many factors contributing to both the domestic and international failures. From their comments and commentaries, it become clear that individual initiative and the African based solution would is the only hope to resolve the problem of nation building in Somalia. Free market initiatives from the people themselves, as well as self-help social and educational programs; have already begun to appear out of the chaos. Given time, patience, and non-intrusive support from others, the Somalian have the potential to make these programmes successfully for nation building.